Potentially Toxic Elements in Urban-Grown Lettuce: Effectiveness of Washing Procedures, Risk Assessment, and Isotopic Fingerprint - Camila Neves Lange; Bruna Moreira Freire; Lucilena Rebelo Monteiro; Marycel Elena Barboza Cotrim; Bruno Lemos Batista (Plants)
This study investigates the presence of potentially toxic elements (PTEs) in lettuce (Lactuca sativa L.) grown in urban gardens in a highly industrialized city in Brazil and evaluates the effectiveness of different washing methods in reducing contamination. Ten elements (arsenic (As), barium (Ba), cadmium (Cd), cobalt (Co), chromium (Cr), copper (Cu), nickel (Ni), lead (Pb), vanadium (V), and zinc (Zn)) were analyzed for their concentration, and a health risk assessment was performed. The results showed that Pb concentrations in lettuce from gardens near the Capuava Petrochemical Complex reached 0.77 mg kg−1, exceeding both national and international safety limits. The most effective washing procedure involved the use of sodium hypochlorite, which reduced As by 46%, Pb by 48%, and V by 52%. However, elements such as Ba, Cd, Cr, and Ni showed limited reductions of less than 10% across all washing methods. Health risk assessments revealed a particular concern for children, with the total cancer risk (TCR) exceeding acceptable limits in some gardens. Isotopic analysis of Pb revealed that atmospheric pollution from gasoline emissions and industrial activities were the primary sources of contamination. The elevated levels of Pb, Cr, and As highlight the need for targeted health education in local communities, especially regarding the importance of proper washing techniques. Risk management strategies, including improved contamination control and public awareness, are crucial to minimize exposure to these harmful elements, particularly in vulnerable populations like children.